GR_GERICHTE SK1 2023 12 vom 22. Januar 2024 , Alters-/Hinterbliebenenvers. - GR Gerichte (2024)
mehrfache Gewalt und Drohung gegen Behörden und Beamte gemäss Art. 285 Ziff. 1 Abs. 1 StGB | StGB 285-294 Öffentliche Gewalt